If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 67 + -2x = 16x + 17 Reorder the terms: 67 + -2x = 17 + 16x Solving 67 + -2x = 17 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 67 + -2x + -16x = 17 + 16x + -16x Combine like terms: -2x + -16x = -18x 67 + -18x = 17 + 16x + -16x Combine like terms: 16x + -16x = 0 67 + -18x = 17 + 0 67 + -18x = 17 Add '-67' to each side of the equation. 67 + -67 + -18x = 17 + -67 Combine like terms: 67 + -67 = 0 0 + -18x = 17 + -67 -18x = 17 + -67 Combine like terms: 17 + -67 = -50 -18x = -50 Divide each side by '-18'. x = 2.777777778 Simplifying x = 2.777777778
| x^2+2-15=0 | | 6-8x=206-43x | | 16x^4-x^2=0 | | 91-3x=2x+21 | | 3-12r=-5 | | -49-2x=11-8x | | w+7*5+2= | | M^2-3mn-2n^2= | | 3x+5=-75-7x | | 117-6x=10x+21 | | a^2-10ab-24b^2= | | w^2*.5w-288=0 | | w^2+.5w-288=0 | | 7+5x=39+x | | w(w*.5)-288=0 | | 3x-5=12x-104 | | 5x+32=15x-88 | | 6x+50=10x-14 | | 3x-5=-2x+10 | | n^2-36=0 | | 169k^2-81m^2=0 | | -m^2-m=0 | | P=2x+2l | | 9x^2+10x+2=0 | | 4x=40x | | 6x-4y=18 | | x(x+6)-6=x^2+3x+1 | | 7x+30=3x+50 | | 7(k-3)-(6k-6)=7 | | 220+30=y | | m^2+6m-9=0 | | x^2-63=2x+132 |